Estimating bradykinesia severity in Parkinson's disease by analysing gait through a waist-worn sensor. (1st May 2017) - Samà, A.; Pérez-López, C.; Rodríguez-Martín, D.; Català, A.; Moreno-Aróstegui, J.M.; Cabestany, J.; de Mingo, E.; Rodríguez-Molinero, A.
Abstract: Bradykinesia is a cardinal symptom of Parkinson's disease (PD) and describes the slowness of movement revealed in patients. Current PD therapies are based on dopamine replacement, and given that bradykinesia is the symptom that best correlates with the dopaminergic deficiency, the knowledge of its fluctuations may be useful in the diagnosis, treatment and better understanding of the disease progression. This paper evaluates a machine learning method that analyses the signals provided by a triaxial accelerometer placed on the waist of PD patients in order to automatically assess bradykinetic gait unobtrusively. This method employs Support Vector Machines to determine those parts of the signals corresponding to gait. The frequency content of strides is then used to determine bradykinetic walking bouts and to estimate bradykinesia severity based on an epsilon-Support Vector Regression model. The method is validated in 12 PD patients, which leads to two main conclusions. Firstly, the frequency content of the strides allows for the dichotomic detection of bradykinesia with an accuracy higher than 90%. This process requires the use of a patient-dependant threshold that is estimated based on a leave-one-patient-out regression model. Secondly, bradykinesia severity measured through UPDRS scores is approximated by means of a regression model with errors below 10%. Although the method has to be further validated in more patients, results obtained suggest that the presented approach can be successfully used to rate bradykinesia in the daily life of PD patients unobtrusively. Highlights: A method is proposed to detect and rate bradykinetic gait in an unobtrusive way. A waist-worn triaxial accelerometer, SVM and strides' frequency content are employed. Detection accuracy based on a leave-one-patient-out (LOPO) evaluation is 92%. Severity estimation error through LOPO is ~10%. Results suggest the method can unobtrusively rate bradykinesia in patients' daily life.